Study on closing and cracking stress calculation method of fractured rock - Qiang, Yue; Liu, Gang; Xia, Changsi; Li, Shaohong; Li, Li; Zhao, Dongsheng; Zhou, Ling; Cheng, Longfei (Frontiers in Earth Science, 2023)
Determining the characteristic stress intensity according to the rock stress-strain curve is significant significance for rock engineering. Nowadays, there are relatively mature methods for determining peak stress and damage stress. However, the crack volume strain method, axial strain method, and strain response method are more subjective to determine rock’s closure stress and initiation stress. The closure rock stress and crack initiation stress refined value method are proposed based on these methods, which are based on the discreteness of the rock stress and strain point. Through optimizing the stress characteristics by an objective function (variance function), the subjectivity of artificial observation is avoided; Based on the trend of rock stress-strain curve, an empirical method for determining rock closure stress and crack initiation stress is proposed. The test results indicate that the two proposed methods that calculate closure rock stress and crack initiation stress can obtain reasonable results. These methods can be used as a supplement to the characteristics of the rock stress determination method and can be used in actual engineering.